2009
DOI: 10.1590/s0103-90162009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Shading and periods of acclimatization of micropropagated banana plantlets cv. Grande Naine

Abstract: Banana plantlets obtained by micropropagation need to be submitted to a period of acclimatization since they do not use light, water, and nutrients in an efficient way. The acclimatization must be carried out under greenhouse conditions where temperature, light, and air humidity are adequate for a gradual hardening of the plantlets. In this study, the development of banana plantlets was evaluated during acclimatization under a full light condition including covered surfaces with red shade cloth (70%, 50%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
2
3
0
2
Order By: Relevance
“…CoVC 07-06-05 (20.15) and CoC 671 (27.76) (Table 3). Scaranari et al (2009) reported that shade net (50% shade) facility was optimum for hardening of banana genotypes. They obtained superior performance of plantlets maintained under black coloured 50% shade cloth for nine weeks, both in the summer and winter seasons.…”
Section: Resultsmentioning
confidence: 99%
“…CoVC 07-06-05 (20.15) and CoC 671 (27.76) (Table 3). Scaranari et al (2009) reported that shade net (50% shade) facility was optimum for hardening of banana genotypes. They obtained superior performance of plantlets maintained under black coloured 50% shade cloth for nine weeks, both in the summer and winter seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Na cv. Grande Naine o uso de seis fertirrigações com alternância de MAP, nitrato de cálcio e nitrato de potássio (100 g 100 L -1 ) em mudas cultivadas sob tela de malha preta com 50% de sombreamento por nove semanas, proporcionou o maior crescimento das mudas (Scaranari et al, 2009 Diferenças podem ser identificadas entre cultivares, como a observada no presente trabalho e, conforme verificado por Oliveira et al (2008a) também entre cultivares e híbridos em três ciclos de produção, quando as cvs. Preciosa e Pacovan Ken apresentaram as maiores alturas e os híbridos PA42-44 e FHIA 02, e as cvs.…”
Section: Resultsunclassified
“…Pada lingkungan luar ini, tanaman dipaksa untuk menyerap hara melalui akar dan melakukan fotosintesis untuk tumbuh dan berkembang. Sebagian besar bibit asal kultur jaringan menjadi layu dan tidak bertahan hidup karena kehilangan air lewat transpirasi lebih besar dibandingkan dengan air yang mampu diserap oleh akar (Pospisilova et al, 2007;Scaranari et al, 2009). Pengurangan cekaman dan manipulasi kondisi aklimatisasi perlu dilakukan sehingga tercipta kondisi optimum untuk ketahanan dan pertumbuhan planlet.…”
Section: Pendahuluanunclassified